A ROBUST POSSIBILISTIC APPROACH FOR MULTI-DEPOT INVENTORY ROUTING PROBLEM - Hosseini-Motlagh, Seyyed-Mahdi; Nikkhah Qamsari, AmirSaeed; Ghatreh Samani, Mohammad Reza (International Journal of Industrial Engineering: Theory, Applications and Practice, 2020)
This study proposes a robust model for the inventory-routing problem in which a set of suppliers distribute some products to multiple customers facing uncertain demands over a finite time horizon. Customers' demand has not a specified probability distribution. The only knowledge about the demand of customers is that these uncertain parameters are random variables and can take any value in their determined interval. The suppliers are taking into account for managing the inventory of their customers. Each customer can be allocated to any supplier at any period. The proposed model is to determine the amount of each product that must be delivered to each customer as well as the route and the time. To cope with this type of uncertainty, a robust-possibilistic method is applied in the context of the inventory-routing problem. The efficiency of the proposed model is demonstrated by numerical experiments and some sensitivity analyses.